Impact of Laparoscopic Partial Nephrectomy and Open Partial Nephrectomy on Outcomes of Clear Cell Renal Cell Carcinoma - Yu, Feng; Xu, Qian; Liu, Xian-Gen (Frontiers in Surgery, 2021)
Objective: To analyze the impact of laparoscopic partial nephrectomy (LPN) and open partial nephrectomy (OPN) on outcomes of complex clear cell renal cell carcinoma (ccRCC). Methods: A total of 132 high-complex ccRCC patients with a Radius Exophytic Nearness Anterior Location (R.E.N.A.L) score ≥7 enrolled in our hospital between January 2018 and June 2020 were matched and assigned to an LPN group (given LPN treatment) and an OPN group (given OPN treatment), with 66 cases in each group. Two weeks and 3 months after the operation, the renal indexes, inflammatory factors, basic perioperative conditions, and incidence of complications were compared. Results: Two weeks after the operation, the levels of SCr and CysC were elevated, with higher levels observed in the LPN group (all P < 0.05), and the eGFR levels were reduced, with a lower result in the LPN group. Three months after the operation, the two groups observed decreased levels of SCr and CysC, and an increased level of eGFR; moreover, the decreased SCr and CysC levels were still higher, and the increased eGFR was lower than those before the operation (P < 0.05). The levels of CRP and TNF-α in the two groups increased after the operation, with a lower outcome in the LPN group (P < 0.05). Moreover, the LPN group had less intraoperative blood loss and shorter postoperative length of hospital stay but longer blocking time compared to the OPN group (P < 0.05). Patients in the LPN group were recorded with a lower complication incidence compared with the OPN group (3.03 vs. 15.15%, P < 0.05). Conclusion: Both LPN and OPN enjoy significant efficacy in the treatment of complex ccRCC and effectively protect renal function. Moreover, LPN is a more acceptable option for complex ccRCC due to its numerous benefits in postoperative stress response, complications, recovery. which is worthy of promotion with safety and feasibility.